Does environmental disclosure relate to environmental performance? Reconciling legitimacy theory and voluntary disclosure theory - Zeeshan Mahmood; Zubair Ahmad; Waris Ali; Aneela Ejaz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
This paper seeks to understand the relationship between corporate environmental disclosure and corporate environmental performance in a Pakistani context. Also, this paper aims to understand whether patterns of environmental disclosure varies between the different categories (good, bad and mixed) of environmental performance. The data were taken from the annual reports and sustainability reports of 78 sample firms listed on a Pakistan stock exchange for the year 2014 and 2015. The empirical results indicate that environmental disclosure is significantly associated with environmental performance. Both Good performers and Bad performers have increased their level of disclosure toward environmental concern as compared to mixed performers. The increase in the level of disclosure by good performers can be explained through the voluntary disclosure theory as an attempt to differentiate themselves from others. The increase in the level of disclosure by bad performers can be explained through legitimacy theory as an attempt to change the public perception. The findings of this paper are of practical importance to the investors and other regulatory authorities as they should be cautious while interpreting increase in disclosures related to environmental activities. This study provides empirical evidence that an increase in environmental disclosure may not be a valid signal to differentiate the Good and Bad environmental performers.
Keywords: 330; environmental disclosure; environmental performance; environmental accounting; legitimacy theory; voluntary disclosure theory; Pakistan